Fiscal hangover : how to profit from the new global economy - Fitz-Gerald, Keith (Hoboken, N.J. : John Wiley & Sons, 2010)
This book is for the millions of disillusioned investors around the world who, dispite being taken on a white-knuckle ride they didn't deserve, know that the way forward is through a better understanding of how we got here and what it will take to get ahead in the new global economy. if only someone would show them the way.
Includes bibliographical references (p. 309-315) and index.
Tặng
Keywords: Finance, Personal; Financial crises; International finance; Investments